Araceae root and citrus fibers tend to decrease Escherichia coli adhesion and myeloperoxidase levels in weaned piglets - Tanghe, Sofie; De Vos, Maartje; Degroote, Jeroen; Lannoo, Kobe; Vande Ginste, Jan; D'Inca, Romain; Michiels, Joris (Frontiers in Veterinary Science, 2023)
Introduction Weaning is a stressful experience in the piglet's life, and it often coincides with impaired gut health. Post-weaning diarrhea in piglets is frequently caused by enterotoxigenic Escherichia coli (E. coli). The first step of an E. coli infection is the adhesion to host-specific receptors present on enterocytes, leading to pro-inflammatory immune responses. The aim of this study was to examine if specific fiber fractions in the piglet diet can prevent E. coli adhesion and subsequent immune responses. Methods The trial included 200 piglets (Danbred × Piétrain): 10 piglets/pen × 10 pens/dietary treatment × 2 dietary treatments. From weaning until 14 days (d14) post-weaning, piglets were fed a control diet or test diet with 2 kg/ton of a mixture of specific fiber fractions derived from Araceae root and citrus. Afterwards, 1 piglet per pen was euthanized, a section was taken at 75% of small intestinal length and E. coli colonization on the mucosal epithelium was quantified by scraping and conventional plating. From the same small intestinal section, histo-morphological indices were assessed, and mucosal scrapings were analyzed for gene expression of pro- and anti-inflammatory cytokines, and NF-kB. Analyses of specific intestinal bacteria and SCFA were performed on samples of intestinal content (small intestine, caecum, colon). Fecal samples were taken to measure myeloperoxidase (MPO), calprotectin and PAP/RAG3A as biomarkers for intestinal inflammation. Results and discussion Piglets fed the fiber mixture tended to have decreased E. coli colonization to the mucosal epithelium (5.65 vs. 4.84 log10 CFU/g; P = 0.07), less E. coli in the caecum (8.91 vs. 7.72 log10 CFU/g; P = 0.03) and more Lachnospiraceae in the colon (11.3 vs. 11.6 log10 CFU/g; P = 0.03). Additionally, the fiber mixture tended to increase cecal butyric acid (10.4 vs. 19.1 mmol/kg; P = 0.07). No significant effect on histo-morphological indices and on gene expression of pro- and anti-inflammatory cytokines and NF-kB was observed. The fecal MPO concentration tended to decrease (20.2 vs. 10.4 ng/g; P = 0.07), indicating less intestinal inflammation. In conclusion, this study showed that specific fiber fractions from Araceae root and citrus in piglet weaner diets may decrease the risk of pathogen overgrowth by reducing E. coli adhesion and intestinal inflammation.